Short Communication: Bird species in the cement factory complex of Tarjun, South Kalimantan, Indonesia - MAULANA KHALID RIEFANI; MOCHAMAD ARIEF SOENDJOTO; ANDY M. MUNIR (Society for Indonesian Biodiversity, 2019)
Riefani MK, Soendjoto MA, Munir AM. 2019. Bird species in the cement factory complex of Tarjun, South Kalimantan, Indonesia. Biodiversitas 20: 218-225. The factory complex of PT Indocement Tunggal Prakarsa Tbk., Tarjun, South Kalimantan, Indonesia consists of cement manufacturing plants and employee settlements. Supporting facilities for the two main areas are open spaces in the form of waters (lakes, small rivers), grasslands (golf courses, grassy fields with several woody individuals growing on it), and forests (mangrove forests, secondary lowland forests, including shrubs). However, the data related to bird species that live in complex are not available yet. The purpose of this study was to inventory bird species in the ITP complex and to analyze qualitatively the presence of birds. These data will be used as a baseline for the development of the complex, comparative data for birds in the operational area of mining located 27 km outside the complex, and the completeness of the requirements for submitting a company performance rating (Proper). Birds were inventoried four periods between 2015-2016 at 06:00 - 08:00 and 16:30 - 18:00. The period here was treated as repetition. Observers equipped with binoculars and telephoto cameras walked around through footpaths and roads exploring the whole complex. In water and grassland areas, birds recorded can be at an observation distance of more than 50 m, whereas in forest areas, birds recorded were at a maximum distance of 50 m. A total of eighty-seven species and 41 families of birds were recorded. Of them, eighteen species and 8 families are waterbirds.The most recorded birds were classified as residents. All of the birds were recorded or observed easily every day or almost every day, at least at the research sites. Others (8 species) wee categorized as migratory birds. Fourteen species are protected by the Regulation of the Minister of Environment and Forestry, the Republic of Indonesia No. P.92/MENLHK/SETJEN/KUM.1/8/2018, 30 August 2018.